Arginase inhibition improves endothelial function in patients with type 2 diabetes mellitus despite intensive glucose‐lowering therapy. (27th August 2018) - Mahdi, A.; Kövamees, O.; Checa, A.; Wheelock, C. E.; von Heijne, M.; Alvarsson, M.; Pernow, J.
Abstract: Background: Arginase is implicated in the pathogenesis behind endothelial dysfunction in type 2 diabetes mellitus (T2DM) by its inhibition of nitric oxide formation. Strict glycaemic control is not sufficient to improve endothelial function or cardiovascular outcomes in patients with T2DM, thus other treatment strategies are needed. We hypothesized that arginase inhibition improves endothelial function beyond glucose‐lowering therapy following glucose optimization in patients with poorly controlled T2DM. Methods and results: Endothelial function was evaluated in 16 patients with poorly controlled T2DM (visit 1) and 16 age‐matched controls using venous occlusion plethysmography. T2DM patients were re‐evaluated (visit 2) after intensive glucose‐lowering regimen. Endothelium‐dependent (EDV) and ‐independent (EIDV) vasodilatations were evaluated before and after 120 min intra‐arterial infusion of the arginase inhibitor N(ω)‐hydroxy‐nor‐L‐arginine (nor‐NOHA). HbA1c was reduced from 87 ± 17 (visit 1) to 65 ± 11 mmol mol −1 (visit 2, P < 0.001). Basal EDV, but not EIDV, was significantly lower in patients with T2DM than in healthy subjects ( P < 0.05). EDV and EIDV were unaffected by glucose‐lowering regimen in patients with T2DM. Arginase inhibition enhanced EDV in T2DM patients both at visit 1 and visit 2 ( P < 0.01). There was no difference in improvement in EDV between the two occasions. EIDV was unaltered by nor‐NOHA in T2DM at visit 1, but was slightly improved at visit 2. Conclusions: Arginase inhibition improves endothelial function in patients with poorly controlled T2DM, which is maintained following glucose optimization. Thus, arginase inhibition is a promising therapeutic target beyond glucose lowering for improving endothelial function in T2DM patients.